1989
DOI: 10.1073/pnas.86.10.3828
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord blood as a potential source of transplantable hematopoietic stem/progenitor cells.

Abstract: The purpose of this study was to evaluate human umbilical cord blood as an alternative to bone marrow in the provision of transplantable stem/progenitor cells for hematopoietic reconstitution. Although no direct quantitative assay for human hematopoietic repopulating cells is at present available, the granulocyte-macrophage progenitor cell (CFU-GM) assay has been used with success as a valid indicator of engrafting capability. We examined greater than 100 collections of human umbilical cord blood for their con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
541
0
38

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,076 publications
(585 citation statements)
references
References 42 publications
6
541
0
38
Order By: Relevance
“…tor cells at similar or higher frequency than that of BM. 1,[7][8][9]12 Therefore, UCB, which is normally discarded, has been evaluated as a source of progenitor cells that can be used for the treatment of diseases potentially curable by bone marrow transplantation (BMT). [2][3][4] Major concerns for wider transplant application of UBC have been related to the low total number of progenitor cells obtained by a single collection.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…tor cells at similar or higher frequency than that of BM. 1,[7][8][9]12 Therefore, UCB, which is normally discarded, has been evaluated as a source of progenitor cells that can be used for the treatment of diseases potentially curable by bone marrow transplantation (BMT). [2][3][4] Major concerns for wider transplant application of UBC have been related to the low total number of progenitor cells obtained by a single collection.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3] Studies are under way to determine the feasibility of UCB banking for use in unrelated transplants. [3][4][5][6] However, the major concern for future transplant application in adult patients has been related to the low number of progenitor cells that could be obtained by a single UCB collection.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies by Knudtzon [2] demonstrated that granulocytic colony-forming cells could be grown in vitro from UCB. Further in vitro studies by Broxmeyer et al [3] established that UCB contains a sufficient number of hematopoietic stem/progenitor cells to be used for autologous or allogeneic hematopoietic reconstitution. In 1989, Gluckman and colleagues published results from the first successful UCB transplant using cord blood from an HLAidentical sibling in a patient with Fanconii's anemia [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the most recent studies, research has been essentially based on the use of mesenchymal stem cells isolated from the umbilical cord blood, umbilical cord matrix and bone marrow. 17,18 However, it is important to highlight that there is still a long way to go in this area, and subsequent studies should demonstrate unequivocally (a) differentiation into functional somatic cells that integrate into existing tissues allowing recovery in vivo; (b) the non-formation of tumors; (c) the availability in sufficient number (and/or consequent expansion) of useful cells; and (d) that the results reported are reproducible in a variety of scientific and clinical settings (this has been a main cause of concern in the field).…”
Section: Stem Cell Research: Ethics and Scientific Crossroadsmentioning
confidence: 99%